Transplantation and innate immunity: the lesson of natural killer cells - Bertaina, Alice (BioMed Central, 2009)
Natural killer cells have been demonstrated to play a major role in mediating an anti-leukemia effect in patients given a T-cell depleted allogeneic hematopoietic stem cell transplantation from an HLA-haploidentical family donor. In particular, donor-derived natural killer cells, which are alloreactive (i.e. KIR/HLA mismatched) towards recipient cells, significantly contribute to the eradication of leukemia blasts escaping the preparative regimen to transplantation. A recent study on high-risk pediatric acute lymphoblastic leukemia refractory to chemotherapy further highlighted the importance of donors with alloreactive natural killer cells in haploidentical hematopoietic stem cell transplantation, as it demonstrated that these cells can emerge starting from the fourth-fifth month after the allograft and persist for many months. This study represents a major breakthrough in the cure of otherwise fatal leukemias, providing information on the best criteria for choosing the optimal donor.